From Conversion to Fellowship: The Hindu Christian Encounter in the Gandhian perspective - Vazhappllly, Johnson (Journal of Dharma, 1992)
A. Pushparajan, From Conversion to Fellowship: The Hindu Christian Encounter in the Gandhian perspective, Varanasi: St. Paul's Society, Allahabad, 1 990, pp. 350 Rs. 95 (paper) Rs. 125 (Hard).